Pengaruh Laba Akuntansi, Arus Kas Operasi Dan Ukuran Perusahaan Terhadap Financial Distress Pada Emiten Asuransi Di Bursa Efek Indonesia - Umam, Danang Choirul; Fahmi, Darul; Halimah, Imar (Prisani Cendekia, 2024)
This This study aims to investigate the influence of accounting profit, operating cash flow, and firm size on the risk of financial distress in insurance companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022. The analytical method used is logistic regression to measure the impact of the independent variables on the dependent variable. This research is expected to contribute to the management of insurance companies in designing effective financial strategies and provide important information for regulators and capital market stakeholders. The results of the study indicate that operating cash flow has a significant effect on financial distress. Conversely, accounting profit and firm size do not show a significant effect on financial distress. Based on these findings, it is recommended that insurance companies adopt comprehensive and proactive management strategies, including effective cash flow management, revenue diversification, comprehensive risk management, and operational efficiency improvements to help manage financial distress risk and achieve long-term financial stability.